Mitochondrial dynamics caused by QoIs and SDHIs fungicides depended on FgDnm1 in Fusarium graminearum - Jin-bo KANG; Jie ZHANG; Yin-kai LIU; Ji-chang SONG; Jian-lin OU; Xian TAO; Ming-guo ZHOU; Ya-bing DUAN (Journal of Integrative Agriculture, 2023)
Fusarium head blight (FHB) caused by Fusarium graminearum is a devastating fungal disease on small grain cereal crops, because it reduces yield and quality and causes the mycotoxin contamination to the grain. Dynamins and dynamin-related proteins (DRPs) are large GTPase superfamily members, which are typically involved in the budding and division of vesicles in eukaryotic cells, but their roles in Fusarium spp. remain unexplored. Here, we found that FgDnm1, a DRP and homolog to Dnm1 in Saccharomyces cerevisiae, contributes to the normal fungal growth, sexual reproduction and sensitivity to fungicides. In addition, we found FgDnm1 co-localizes with mitochondria and is involved in toxisome formation and deoxynivalenol (DON) production. Several quinone outside inhibitors (QoIs) and succinate dehydrogenase inhibitors (SDHIs) cause fragmentated morphology of mitochondria. Importantly, the deletion of FgDnm1 displays filamentous mitochondria and blocks the mitochondrial fragmentation induced by QoIs and SDHIs. Taken together, our studies uncover the effect of mitochondrial dynamics in fungal normal growth and how such events link to fungicides sensitivity and toxisome formation. Thus, we concluded that altered mitochondrial morphology induced by QoIs and SDHIs depends on FgDnm1.